ANALISIS ATRAKSI INTERPERSONAL MAHASISWA PENGGUNA APLIKASI TINDER - Syifa Nabila Al Kautsar; Poppy Febriana (Jurnal Ranah Komunikasi, 2022)
New media consitutes a new era from the media which continues to grow with various function that can be it will facilitate human especially in communicating. Communication was not only done to exchange information, but also as an intermediary in a relationship with other human. Even with the new media, a person can have a partner simply by making communication indirectly through digital platform. And one of them is Tinder, an application that designed to find a perfect partner for its user. It confront users who share the same passion for things they like and facilitates them a private room chat as a medium to get closer to each other. However, not all users end up in a romantic relationship. Therefore, this study will discuss what factors can affect a person's attraction to other people that allow them to establish a relationship. This study uses a netnographic method with a qualitative approach. The results of this study indicate that the main factors that influence a person to want to have a relationship with another person are due to the similarity of personal characteristics and having known or been close to that person before thus enabling them to establish relationships.